Hubungan Tingkat Pengetahuan Masyarakat dengan Perilaku Pencegahan Malaria di Dusun SP1, Desa Saritani, Kecamatan Wonosari, Kabupaten Boalemo - Nur Ain Shytiawaty Hilahapa; Dion Kunto Adi (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
This study aims to determine the relationship between the community’s level of knowledge and malaria prevention behavior in SP1 Hamlet, Saritani Village, Wonosari District, Boalemo Regency. This research is an analytical study with a quantitative approach using a cross-sectional design. The population consisted of all residents in SP1 Hamlet, with a total sample of 100 respondents selected through simple random sampling. Data were collected using a structured questionnaire covering knowledge about malaria and preventive behaviors. Data analysis was conducted using the Chi-Square test and simple linear regression. The results showed a significant relationship between the level of knowledge and malaria prevention behavior (p-value < 0.05). The higher a person’s knowledge about the causes, transmission, and prevention of malaria, the better their preventive behavior. The simple linear regression analysis also indicated that knowledge has a positive influence on prevention behavior. Therefore, improving community knowledge through health education and counseling programs is essential to strengthen malaria prevention efforts and reduce the incidence rate in the area.